Android-Based "Idea Bank" Application as Media E-Learning in Courses Change Management - Elfia Nora; Afwan Hariri Agus Prohimi; Lohana Juariyah (Journal of Disruptive Learning Innovation (JODLI), 2020)
During this time for change management lectures, it is still often conveyed by the method of lectures and group discussions on cases of change in the industry and its management. Idea Bank application will be expected to be a reference for students to pour ideas of change, try to design changes, keep documentation of the implementation of changes they make, so that the idea of changes and innovations made by students in this application later may also be useful for the State University of Malang, because during this time the tasks carried out by students are more often stored in hard copy, or soft copy personally by lecturers who foster the subject.The purpose of developing e-learning media in change management courses in the form of android-based "idea bank" application is to create more innovative electronic learning media and provide more interactive learning media to students in accordance with the millennial era they live in.Learning tools developed in the form of Electronic Learning Media Applications stored on HP Android can be installed through the Play Store labeled "Idea Bank", where in it there will be several features namely problem portrait feature,  Idea Change feature, Idea Design feature,  theory change feature, Idea Succes feature, and some electronic program tools, including save menu, table data filling menu, upload documentation and others.The development method is Borg & Gall development model (1996) using water fall flow at the development stage. Stages of development ranging from needs analysis, product planning, product development, trial / implementation (validation), revision and report creation.Product results in the form of Idea Bank Application in the form of problem portrait feature, Idea Change feature, Idea Design feature, theory change feature Idea Succes Feature. stored on HP Android and also application usage tutorial.Keywords: Application; Idea Bank; E-learning.